An innovative approach for detection of isomorphism of epicyclic gear trains. (2020) - Mustafa, Jiyaul; Hasan, Ali; Khan, R.A.
Abstract: Detection of isomorphism in epicyclic gear trains (EGTs) and their mechanisms has been a great challenge for several researchers since few years. Checking for isomorphism at the conceptual stage will avoid duplication in the generation process. In this paper, an innovative approach based on Modified gradient method (MGM) is presented for identification of isomorphism of epicyclic gear trains and inversions of mechanisms. The new concept 'MGM' is proposed on basis of Train values and connectivity Matrices to be a quantitative measurement of isomorphism in EGTs. This is a novel, simple algorithm and less computation required to detect the duplication of EGTs. The proposed algorithm is applied to various examples from 4-links, 5-links, 6-links, and 8-links 1-DOF of the epicyclic gear trains. All the examples have been found satisfactory results with existing literature.